If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x = 5 + -4 Combine like terms: 5 + -4 = 1 3x = 1 Solving 3x = 1 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '3'. x = 0.3333333333 Simplifying x = 0.3333333333
| 3x-5+2x=20 | | 12x+5=4x+3 | | 3x-3-4=5 | | r^2-24=0 | | 46+2x=6x+8x+10 | | 1.35m+0.03=7.80 | | y=100x+400 | | 4(6n-4)=128 | | 2m-5=37 | | 4x+18=6x-2 | | 2a+5(a+3)= | | -8(1-7n)=216 | | 3(7x+8)+6(4x+9)=213 | | 3-4(x+7)=13 | | 6x-10+4x+30=50 | | 2(x-7)+12=24 | | 110=5(-8+6x) | | 4(y+2)=332 | | 3x+5(x-9)=12 | | 8(x-5)=34 | | -8n+2(-5n+3)=-12 | | -8(2+7x)=-240 | | 6(y-2)+4=46 | | 6+29=8x+13 | | -5n-6n= | | (2x+6)(3)= | | -15=3x-8x | | 5p-7=2p+12 | | 12=4-4n+3n | | s=1156+-16t^2 | | 2x-10y^2=0 | | 7x-8=5x+11 |